2006
DOI: 10.1166/jnn.2006.373
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube—Poly(3-Octylthiophene) Composite Photovoltaic Cells

Abstract: The effects of varying nanotube loading/concentration in carbon nanotube-poly(3-octylthiophene) blends used as thin film photovoltaic cells, have been studied. The network of single walled nanotubes clearly aids in exciton separation and modifies carrier mobility within the active layer as suggested by a bulk heterojunction model. Further, modifications to the metal-polymer interface occur with the addition of nanotubes leading to variations in the observed VOC of the photovoltaic cells. Finally, the "nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Several groups have exploited the possibility of using SWCNT to improve carrier generation and collection efficiency in bulk heterojunction [20][21][22][23][24][25][26][27][28][29][30][31] and photoelectrochemical solar cells. 32 33 Investigations of the excited state properties have demonstrated that the favorable energy levels and high electron affinity of SWCNT result in the creation of long-lived radical ion-pairs after excitation of the organic semiconductor chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have exploited the possibility of using SWCNT to improve carrier generation and collection efficiency in bulk heterojunction [20][21][22][23][24][25][26][27][28][29][30][31] and photoelectrochemical solar cells. 32 33 Investigations of the excited state properties have demonstrated that the favorable energy levels and high electron affinity of SWCNT result in the creation of long-lived radical ion-pairs after excitation of the organic semiconductor chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…A more commonly adopted way to increase efficiency is using CNT as doping material for polymer/fullerene bulk heterojunction based solar cell. , The introduction of CNTs into the polymer/fullerene bulk heterojunction improves the power conversion efficiency even without annealing, suggesting that the presence of CNTs either ameliorates the nanoscale morphology or improves the carrier mobility . Experimental studies indicate that the performance of organic solar cells can be dramatically enhanced after introduction of proper amount of CNTs to active layer, , while an excessive amount of CNTs, on the other hand, reduces the efficiency due to the increased bimolecular recombination as well as possible circuit shorting .…”
mentioning
confidence: 99%